Threatening and nurturing mental health: insights from Danish elite athletes on the dynamic interplay of factors associated with their mental health - Küttel, A.; Storm, L. K.; Stambulova, N.; Henriksen, K. (Frontiers in Sports and Active Living, 2024)
Introduction: Numerous factors have been identified that potentially influence athletes' mental health. Given the predominant focus in the literature on athletes' mental health risk factors, our study aimed to explore elite athletes' perceptions of factors associated with their mental health and thriving based on the combination of holistic developmental and ecological approaches.